Criminal Law Enforcement Against Oil Spills by Foreign Ships Case Study of Arman 114 Motor Tanker in the North Natuna Sea - Muhammad Buzjany Dzikry; Henry Aspan; Mhd. Azhali Siregar (Cattleya Darmaya Fortuna, 2026)
The North Natuna Sea is a strategically important maritime region for Indonesia due to its economic, ecological, and geopolitical significance. The increasing intensity of international shipping activities has heightened the risk of marine pollution, particularly oil spills caused by foreign vessels, posing serious threats to marine ecosystems and national maritime security. One of the most significant cases is the oil spill involving the foreign-flagged Motor Tanker (MT) Arman 114, which highlights the complexity of criminal law enforcement against transnational environmental crimes. This study aims to analyze the mechanism of criminal law enforcement applied to the MT Arman 114 case and to evaluate the contribution of the court's decision to marine pollution prevention in Indonesia. This research employs a normative legal method using statutory, conceptual, and case approaches by examining national legislation, international legal instruments, legal doctrines, and relevant court decisions. The findings reveal that Indonesia possesses a comprehensive legal framework through Law Number 32 of 2009 concerning Environmental Protection and Management, Law Number 17 of 2008 concerning Shipping, the Indonesian Criminal Code, and the MARPOL 1973/1978 Convention. Nevertheless, the effectiveness of criminal law enforcement remains constrained by scientific evidentiary challenges, limited maritime surveillance capacity, overlapping institutional authority, jurisdictional complexities involving foreign-flagged vessels, and international diplomatic considerations. The novelty of this study lies in integrating environmental criminal law, maritime law, and international maritime legal obligations to evaluate the practical implementation of criminal law enforcement through the MT Arman 114 case, while also assessing the role of judicial decisions in strengthening legal certainty, environmental protection, and deterrence against future marine pollution offenses. The study concludes that strengthening institutional coordination, technological capacity, legal harmonization, and international cooperation is essential to improve the effectiveness of criminal law enforcement and ensure sustainable protection of Indonesia's marine environment.